Vital Signs Monitoring Device with BPM and SpO2 Notification Using Telegram Application Based on Thinger.io Platform - Sari Luthfiyah; Elga Rahmah Ramadhani; Tri Bowo Indrato; Anan Wongjan; Kamilu O. Lawal (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
Vital signs are an important component of monitoring the adult or child patient's progress during hospitalization, as they allow for the prompt detection of delayed recovery or adverse events. Vital signs are measured to obtain basic indicators of a patient's health status. The most common intervention performed in hospital medicine is a measurement of vital signs, and these traditionally consist of blood pressure, temperature, pulse rate, and respiratory rate. Advanced monitoring systems incorporate a balanced combination of clinical and technological aspects to give an innovative healthcare outcome. Remote patient monitoring systems are rapidly becoming the core of healthcare deliveries. The paradigm shifted from traditional and manual recording to computer-based electronic records and further to smartphones as versatile and innovative healthcare monitoring systems. This research aims to design a Vital Sign Monitoring device for BPM and SpO2 Parameters with Notifications through the IoT-Based Telegram application. This device can monitor vital signs, especially BPM and SPO2, wherever the patient is and whenever so that doctors or health workers and patients can find out their health condition. This display can be viewed via web thinger.io, then forwarded to telegram if an abnormal patient condition is found, and there is an indicator light that will light up differently for each condition. This study uses the MAX30100, which is a digital sensor to detect oxygen saturation and heart rate. The results of this study have succeeded in displaying data on the IoT web and sending notifications to the Telegram application. And also, the resulting data has an error that does not exceed the allowable limit according to each parameter. The difference between heart rate readings and oxygen saturation values ​​on the device and patient monitor is 0.015% for heart rate and 0.01% for oxygen saturation. This study indicates that it is time to monitor vital signs that can be seen remotely and have a system that is an inexpensive and easy-to-operate device for health workers without interfering with activities of daily living.